Challenges Faced by Older Employees in the Era of Open Artificial Intelligence and Strategies to Empower Them - Md. Moyazzem Hossain; Faruq Abdulla; Mohammed Nazmul Huq (Health Care Science)
ABSTRACT The integration of artificial intelligence (AI) into various sectors has undoubtedly brought about numerous benefits, from increased efficiency to innovative problem‐solving. The growing influence of AI across several industries may help to achieve the sustainable development goals (SDGs). However, due to the AI revolution happening in industries across the globe, older employees are often confronted with significant hurdles in keeping pace with these changes. The threat of job displacement looms large as automation driven by AI encroaches upon routine tasks previously performed by human workers. Job insecurity, that is, worry of losing one's job encompasses anxiety, and uneasiness, and affects the mental health of employees. To address these challenges and empower older employees in the era of open AI, it is imperative that organizations implement targeted strategies tailored to their unique needs and circumstances. Employees use the opportunities for continued education provided to them with company support to prevent unwanted effects. organizations can create an inclusive and supportive environment where older employees are empowered to embrace the opportunities presented by AI while leveraging their experience and expertise to drive innovation and success.